Research of the Influence of Tooth Profile Modification on the Tooth Surface Vibration Noise of Automobile Transmission Gear - Pan Haibo (Jixie chuandong)
Aiming at the problem of gear tooth surface vibration noise in automotive transmission,the system vibration model of gear meshing with the gear is established,and the error amount and modification amount of gear tooth profile model are associated,and gear tooth profile in the top of part and the root part is coupled and established,then analysis of vibration and noise is carried out by experimental platform of gear meshing vibration system dynamic model. Through the experiment analysis,it is found that gear meshing noise is an important factor affecting the size and orientation of overall waveform,the modification of gear noise waveform amplitude with respect to time domain fitting before modification is weakened,the impact decreased significantly.At the same time,the main test box vibration and noise are collected by real- time to contrast the noise samples before and after the modification. It is verified the feasibility of system vibration model and the modification method,and a reference for the study of automobile gearbox noise is provided.